2021
DOI: 10.1002/jpen.2112
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐year outcomes of intestinal failure–associated liver disease in children with short‐bowel syndrome: 97% transplant‐free survival and 81% enteral autonomy

Abstract: Our aim was to analyze the outcomes in children with short‐bowel syndrome (SBS), parenteral nutrition dependence (PND), and intestinal failure–associated liver disease (IFALD) treated in our Intestinal Rehabilitation Program (IRP) during 2007–2018. We retrospectively reviewed charts of 135 patients with SBS‐PND at the time of enrollment in IRP; of these, 89 (66%) had IFALD, defined as conjugated bilirubin (CB) of ≥2 mg/dl at enrollment and/or abnormal liver biopsy showing stage 2–4 fibrosis. Outcomes included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…An increased mortality is reported in patients with IFALD compared to those without it and in children with a more advanced disease. The 3-year survival rate reported is 86% even if Torres et al have recently reported an overall survival of 97% with 81% of patients achieving enteral autonomy in SBS children on low dose of SO-LEs ( 31 33 ).…”
Section: Clinical and Histological Manifestationsmentioning
confidence: 99%
“…An increased mortality is reported in patients with IFALD compared to those without it and in children with a more advanced disease. The 3-year survival rate reported is 86% even if Torres et al have recently reported an overall survival of 97% with 81% of patients achieving enteral autonomy in SBS children on low dose of SO-LEs ( 31 33 ).…”
Section: Clinical and Histological Manifestationsmentioning
confidence: 99%
“…In fact, a 360-degree multidisciplinary evaluation of the patient state is key to orienting management. Within an IRP, liver-sparing PN is commenced to lower the risk of the alarming IFALD [4][5][6]. Moreover, oral feeding is usually preferred since it more closely resembles the natural physiology, stimulating the bowel mucosa, enhancing adaptation and promoting brain learning.…”
Section: Intestinal Rehabilitation Programmentioning
confidence: 99%
“…This has mainly been due to improved overall care, new total parenteral nutrition (TPN) formulas, and improved surgical techniques [4,5]. However, TPN complications are still a challenge for rehabilitation teams and long-term parenteral nutrition (PN) may lead to intestinal failure-associated liver disease (IFALD) [6,7]. The final goal of treatment in these patients should be to achieve enteral autonomy (EA), minimizing complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases require extensive intestinal resection and possibly needing bowel and/or liver transplantation, though the latter is becoming less common with the emergence of specialized intestinal rehabilitation teams and newer therapies, such as bowel lengthening procedures, and treatment with fish oilbased lipid emulsions. [5][6][7][8] Gastroschisis induces a chronic inflammatory state in utero, confirmed by multiple analyses of amniotic fluid and fetal blood. These studies have shown the presence of inflammatory proteins, cells, and cytokines within the amniotic fluid, and the presence of systemic inflammation with elevated inflammatory markers in the fetal blood.…”
mentioning
confidence: 93%